MATHEMATICAL MODELING OF CARDIOINTERVALOGRAHICAL INDICES IN HEALTHY FEMALE JUVENILES WITH HYPOKINETIC TYPE OF HEMODYNAMICS - Ковальчук, В.В. (World of Medicine and Biology, 2014)
The article describes the mathematical models of cardiointervalographical indices in healthy female juveniles with hypokinetic type of hemodynamics based on their anthropometric, somatotypological indices and indices of component composition of body weight. Modeled 15 of 17 investigated cardiointervalographical indices, including 9 models of indices that depend on the total complex of the anthropometric and somatotypological characteristics of the organism more than 50 % – for indices of PNN50, AMo, Max, Min, VAR (variation range of R-R interval), VLF, LF, HF, LF/HF with R2 from 50,4 % to 86,2 %. The highest accuracy of the description of feature models established for group of spectral indices of heart rate variability (R2 from 66,1 % to 79,8 %) and the lowest – for indices of vegetative homeostasis by Baevsky method (R2 from 9,9 % to 41,4 %).
Keywords: healthy female juveniles; hemodynamics; anthropometrical indices; somatotype